Developing English Textbook Based on Students’ Needs for Vocational High School - Arianti, Arin; Nurnaningsih, N; Pratiwi, Veronika Unun (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
The use of English textbook is important to teach students of Vocational High School. Developing English textbook for Vocational students based on the students’ needs. It focuses on English for Academicals Purposes (EAP) which the aim for gaining the higher education/ going to university and English for Occupational Purposes (EOP) which the aim for getting the provisions of job competence. Vocational English textbook covers the students’ needs for those specific purposes. This study uses theoretical perspective method which investigate the learning needs of vocational students and the criteria of textbook for developing English textbook for Vocational High School Students. Some theories in library research is used to search the theories about learners’ needs and vocational textbooks. English textbook which is developed based on the students’ needs is considered as a good English textbook for the students of Vocational High School. It is because the textbook appropriate with the required indicators and relevant to students’ needs.